Preference And Differentiation Among Prophets in Quraan and Sunnah- Objective Study - - Muhammed Shareef Muhammed Othman (Zanco Journal of Humanity Sciences)
The research deals with a study of the verses and correct hadiths mentioned in the matter of preference and differentiation between the prophets. And the beginning is intended for the answer on two questions: The first one is the possibility of  preference between the prophets in mind. The second one is the possibility to prefer between them sharia.